2017
DOI: 10.1080/10580530.2017.1288527
|View full text |Cite
|
Sign up to set email alerts
|

Resource Complementarity and IT Economies of Scale: Mechanisms and Empirical Evidence

Abstract: In this study, we explore economies of scale for IT infrastructure and application services. An indepth appreciation of economies of scale is imperative for an adequate understanding of the impact of IT investments. Our findings indicate that even low IT spending organizations can make a difference by devoting at least 60% of their total IT budget on IT infrastructure in order to foster economies of scale and extract strategic benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…There are, however, several variables influencing the high or low market capitalization and an example is the information published concerning the implementation of corporate governance. The basic framework to predict the reaction of the stock market to this information is explained through the use of signaling theory (Woudstra et al, 2017). Several existing studies have confirmed that stock market rewards companies with more comprehensive corporate governance with high values but there are limited studies on the reasons for this action (Pae & Choi, 2011).…”
Section: Public Interest Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…There are, however, several variables influencing the high or low market capitalization and an example is the information published concerning the implementation of corporate governance. The basic framework to predict the reaction of the stock market to this information is explained through the use of signaling theory (Woudstra et al, 2017). Several existing studies have confirmed that stock market rewards companies with more comprehensive corporate governance with high values but there are limited studies on the reasons for this action (Pae & Choi, 2011).…”
Section: Public Interest Statementmentioning
confidence: 99%
“…There are diverse opinions concerning the definition of intellectual capital and this has led to the identification of the main three elements involved (Mention & Bontis, 2013;Morariu, 2013), and these include human, structural or organizational, and relational or customer capitals. Moreover, the disclosure of the intellectual capital in an annual report showed existing and potential investors the intangible assets owned by a company (Woudstra et al, 2017) and the prediction of the market reaction to the information disclosed can be explained by the signaling theory (Anam et al, 2011).…”
Section: Intellectual Capital Disclosurementioning
confidence: 99%
See 1 more Smart Citation
“…The economical scale is the condition where the output growth is twice as fast as the input, in which if the input price is constant so the cost per unit of output will be lower and the result scale will increase. The companies with a larger output have a different technique with the company having a lower output scale (Woudstra et al, 2017). According to (Irwandi et al, 2019;Sari et al, 2020;Tristiarini et al, 2017), the company emphasizes the theory of economies of scale as a factor that determines the optimal company size and implies the increased profitability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is also discussed that startups, especially in developing nations, use third parties' infrastructure or share IT services in their initial years (Koutsabasis et al, 2008;Nelson et al, 2005). Some of the firms adopt these tools with their current IT configuration and then expand with time as per the requirement and funds (Woudstra et al, 2017;Boja et al, 2012).…”
mentioning
confidence: 99%